Safety and Improved Clinical Outcomes in Patients Treated With New Equine-Derived Heptavalent Botulinum Antitoxin. (27th December 2017) - Yu, Patricia A; Lin, Neal H; Mahon, Barbara E; Sobel, Jeremy; Yu, Yon; Mody, Rajal K; Gu, Weidong; Clements, Jennifer; Kim, Hye-Joo; Rao, Agam K
Abstract : Based on patient experience of equine-derived heptavalent botulinum antitoxin (HBAT), botulism patients treated with HBAT within 2 days of symptom onset had shorter hospital and intensive care stays than those treated later. HBAT should be administered as soon as possible after botulism is clinically suspected. Abstract: Background: Botulism is a rare, life-threatening paralytic illness. Equine-derived heptavalent botulinum antitoxin (HBAT), the only currently available treatment for noninfant botulism in the United States, was licensed in 2013. No reports have systematically examined safety and clinical benefit of HBAT among botulism patients. Methods: From March 2010 through March 2013, we collected data prospectively and through medical record reviews of patients with confirmed or suspected botulism who were treated with HBAT under an expanded-access Investigational New Drug program. Results: Among 249 HBAT-treated patients, 1 (<1%) child experienced an HBAT-related serious adverse event (hemodynamic instability characterized by bradycardia, tachycardia, and asystole); 22 (9%) patients experienced 38 nonserious adverse events reported by physicians to be HBAT related. Twelve (5%) deaths occurred; all were determined to be likely unrelated to HBAT. Among 104 (42%) patients with confirmed botulism, those treated early (≤2 days) spent fewer days in the hospital (median, 15 vs 25 days; P < .01) and intensive care (10 vs 17 days; P = .04) than those treated later. Improvements in any botulism sign/symptom were detected a median of 2.4 days and in muscle strength a median of 4.8 days after HBAT. Conclusions: HBAT was safe and provided clinical benefit in treated patients. HBAT administration within 2 days of symptom onset was associated with shorter hospital and intensive care stays. These results highlight the importance of maintaining clinical suspicion for botulism among patients presenting with paralytic illness to facilitate early HBAT treatment before laboratory confirmation might be available. Clinical consultation and, if indicated, HBAT release, are available to clinicians 24/7 through their state health department in conjunction with CDC.